Optimizing Retail Employee Performance through Organizational Justice and Culture Factors: Mengoptimalkan Kinerja Karyawan Ritel melalui Faktor Keadilan dan Budaya Organisasi - Cahyono Dimas; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2024)
Human resources play a crucial role in organizational progress, with employee performance often measured against set standards. This study investigates the impact of organizational culture and justice on employee performance through job satisfaction at PT. Lion Superindo, a retail company in Sidoarjo. Using quantitative methods, surveys were conducted across three branches, analyzing validity, reliability, and regression. Findings indicate a significant relationship between positive organizational culture, fair treatment, job satisfaction, and enhanced employee performance. These insights emphasize the importance of fostering a positive work environment and fairness to improve employee satisfaction and overall organizational performance. Highlight: Relationship: Unveils significant ties between organizational factors and employee performance. Methodology: Quantitative approach employs surveys and statistical analysis for robust investigation. Implications: Highlights importance of organizational culture and fairness for enhanced performance. Keywoard: Organizational Culture, Organizational Justice, Employee Performance, Job Satisfaction, Retail Industry